Knowledge, attitudes, and practices of hygiene among children in schools of Central Kazakhstan: a cross-sectional study - Ulpan Kuandyk; Alua Omarova; Nailya Delellis (Frontiers in Public Health)
BackgroundThe issue of good hygiene among school-aged children is crucial for public health and sustainable development. Despite the availability of global studies covering countries with different socio-economic conditions, there is a lack of local data reflecting the specifics of Kazakhstan. Therefore, the aim of this study was to determine the level of knowledge, attitude and practice of schoolchildren regarding personal and public hygiene in schools of Central Kazakhstan.MethodsSchool-based cross-sectional study was conducted from September 2024 to December 2024 in six schools of Central Kazakhstan. The simple random sampling technique was used to select the school. A computer-generated sequence of random numbers was used to randomly select students. Subsequently, 382 students aged 11–18 years were selected from a total of 72.179 students. The data were collected through a questionnaire using the online Google forms service. It consisted of socio-demographic data and information on knowledge and practice of personal and public hygiene of students in schools. The data were computerized. A statistical analysis of the data was carried out using SPSS (Statistical Package for Social Sciences). P < 0.05 with a 95% confidence interval was considered statistically significant.ResultsThe results showed significant gender differences in hygiene knowledge and behavior. More than 90% of students knew about the basic rules of personal hygiene, with girls demonstrating higher knowledge and practices compared to boys (e.g., brushing teeth twice a day: 97% of girls vs. 87.8% of boys, P < 0.001). Hand washing before eating was known to 99% of girls and 92.8% of boys (P < 0.05). In terms of hygiene practices, girls brushed their teeth twice a day more often (68.7% of girls vs. 57.5% of boys, P < 0.05). However, there were differences in hygiene compliance at school due to insufficient infrastructure, such as lack of soap, hot water and poor condition of restrooms.ConclusionThe study revealed a high level of knowledge about personal hygiene among school students in Karaganda, especially among girls. However, practical compliance with hygiene rules was often limited by infrastructural problems in schools. Strengthening hygiene education programs and improving sanitary conditions in educational institutions is necessary.